2007
DOI: 10.1093/europace/eum140
|View full text |Cite
|
Sign up to set email alerts
|

Triple-site biventricular pacing in patients undergoing cardiac resynchronization therapy: a feasibility study

Abstract: Triple-site resynchronization appears to be a safe and efficient treatment method, with high response rate. Further studies are needed to evaluate the role of this pacing mode in CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 21 publications
0
28
0
1
Order By: Relevance
“…Until very recently, the only data on triple-site biventricular pacing came from anecdotal case-reports, which suggested that this type of stimulation can improve clinical status and suppress ventricular arrhythmias in HF patients [12][13][14]. In our previous study we demonstrated that dual left-single right cardiac resynchronization is a safe method and can be performed successfully in the majority of CRT candidates [7]. Furthermore, we showed that this type of pacing is highly effective in improving clinical status and echocardiographic parameters in HF patients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Until very recently, the only data on triple-site biventricular pacing came from anecdotal case-reports, which suggested that this type of stimulation can improve clinical status and suppress ventricular arrhythmias in HF patients [12][13][14]. In our previous study we demonstrated that dual left-single right cardiac resynchronization is a safe method and can be performed successfully in the majority of CRT candidates [7]. Furthermore, we showed that this type of pacing is highly effective in improving clinical status and echocardiographic parameters in HF patients.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, any technique which could increase the response rate of resynchronization would be crucial for CRT candidates. Triple-site pacing has been recently proposed as a safe and efficient method of resynchronization [7]. The primary purpose of our study was to compare the safety, procedural course of the implantation procedures and left ventricular leads' performance in the HF patients undergoing triple-site and conventional resynchronization.…”
Section: Introductionmentioning
confidence: 99%
“…Today, the triventricular approach in clinical practice involves implanting two LV leads as far apart as possible (2,16). Success rates of ϳ85% have been reported using available tools (16).…”
Section: Comparison Of Triventricular Pacing Vs Epicardial and Endocmentioning
confidence: 99%
“…Success rates of ϳ85% have been reported using available tools (16). The complicated implant, coupled with the lack of tools to determine the optimal sites and longevity concerns with multiple LV pacing outputs makes this approach difficult to implement in routine clinical practice.…”
Section: Comparison Of Triventricular Pacing Vs Epicardial and Endocmentioning
confidence: 99%
“…A common way to achieve TRIV pacing is to implant the pacing leads at the RV apex, the RVOT, and the LV through the coronary sinus. In a recent study, 37 this technique was performed in 26 patients, and after 3 months, a significant reduction (P < .05) of NYHA class, improvement of exercise capacity, and increased EF were observed. In a preliminary study recently published, 38 54 heart failure patients were enrolled and randomly assigned to either BiV or TRIV mode of pacing.…”
Section: Triventricular Pacingmentioning
confidence: 94%